2021
DOI: 10.1007/s10549-020-06075-6
|View full text |Cite
|
Sign up to set email alerts
|

Concordance of the 21-gene assay between core needle biopsy and resection specimens in early breast cancer patients

Abstract: Background Adjuvant therapy decisions may be partly based on the results of a multigene quantitative reverse transcription-polymerase chain reaction (RT-PCR)-based assay: the 21-gene recurrence score (RS) test of resection specimens. When necessary, core needle biopsy (CNB) may be considered as a surrogate. Here, we evaluated the concordance in gene expression according to results from RT-PCR-based RS testing between paired CNBs and resection specimens. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 81 publications
1
12
0
Order By: Relevance
“…Although many IHC biomarkers such as Ki-67 have been compared in biopsy and surgical specimens, multigene assays are also compared. Although it is not yet a study with the same concept as our study, there are studies that compare the results of the Oncotype DX from biopsy with from the surgical specimen and suggest that Oncotype DX from biopsy results is also concordant and reliable with the surgical specimen [ 32 , 33 ]. As our future study, based on this study, we will begin prognostic study in luminal type and comparison of prognosis between Ki-67 and Oncotype DX or other multigene analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Although many IHC biomarkers such as Ki-67 have been compared in biopsy and surgical specimens, multigene assays are also compared. Although it is not yet a study with the same concept as our study, there are studies that compare the results of the Oncotype DX from biopsy with from the surgical specimen and suggest that Oncotype DX from biopsy results is also concordant and reliable with the surgical specimen [ 32 , 33 ]. As our future study, based on this study, we will begin prognostic study in luminal type and comparison of prognosis between Ki-67 and Oncotype DX or other multigene analysis.…”
Section: Discussionmentioning
confidence: 99%
“… 8 In three smaller studies using matched CNB and SR samples, researchers reported Pearson correlation coefficients ranging from 0.20 to 0.99 and overall concordance ranging from 72.0% to 95.0% using either EndoPredict, GenesWell, or Oncotype Dx multigene assays. 9 , 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
“…However, multigene assays have typically been developed and tested using primary surgical specimens in an adjuvant setting. Only a few studies have determined the performance of multigene assays using CNB in recent years 8–11 . In a large unpaired study, Jakubowski et al found a similar range of Oncotype Dx Recurrence Scores between CNB and surgical resection (SR) samples (10–22 vs. 11–22, respectively) 8 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations